PENGARUH KOMPENSASI, BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN RESTORAN SARI LAUT NELAYAN MEDAN - ekonomi, jurnal; Hiya, Nirmadarningsih (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
Research to determine the influence of compensation, organizational culture, style leadership and work discipline on job satisfaction of Sari Laut Restaurant employees Medan fishermen. With descriptive methods, This type of research is quantitative data, primary data obtained through questionnaires. The sample for this research was 110 employees at the company employee. Analysis uses multiple linear regression models. Results testing which shows that partially or simultaneously the compensation variable, organizational culture, leadership style and work discipline have a positive and significant influence on employee job satisfaction